Evaluasi Program Tahfiz al-Quran Kelas IX di Muhammadiyah Boarding School Pleret - Muhammad Kamal Firdaus (FAI UMY, 2017)
Evaluasi Program Tahfiz al-Quran Kelas IX di Muhammadiyah Boarding School Pleret